The effect of cell growth phase on the regulatory cross-talk between flagellar and Spi1 virulence gene expression. - Chakib Mouslim; Kelly T Hughes (PLoS Pathogens)
The flagellar regulon controls Salmonella biofilm formation, virulence gene expression and the production of the major surface antigen present on the cell surface: flagellin. At the top of a flagellar regulatory hierarchy is the master operon, flhDC, which encodes the FlhD₄C₂ transcriptional complex required for the expression of flagellar, chemotaxis and Salmonella pathogenicity island 1 (Spi1) genes. Of six potential transcriptional start-sites within the flhDC promoter region, only two, P1(flhDC) and P5(flhDC), were functional in a wild-type background, while P6(flhDC) was functional in the absence of CRP. These promoters are transcribed differentially to control either flagellar or Spi1 virulent gene expression at different stages of cell growth. Transcription from P1(flhDC) initiates flagellar assembly and a negative autoregulatory loop through FlhD₄C₂-dependent transcription of the rflM gene, which encodes a repressor of flhDC transcription. Transcription from P1(flhDC) also initiates transcription of the Spi1 regulatory gene, hilD, whose product, in addition to activating Spi1 genes, also activates transcription of the flhDC P5 promoter later in the cell growth phase. The regulators of flhDC transcription (RcsB, LrhA, RflM, HilD, SlyA and RtsB) also exert their control at different stages of the cell growth phase and are also subjected to cell growth phase control. This dynamic of flhDC transcription separates the roles of FlhD₄C₂ transcriptional activation into an early cell growth phase role for flagellar production from a late cell growth phase role in virulence gene expression.